Bright light therapy for mental and behavioral illness: A systematic umbrella review. (1st February 2023) - Reis, Daniel J.; Hoffberg, Adam S.; Stearns-Yoder, Kelly A.; Bahraini, Nazanin H.
ABSTRACT: Bright light therapy (BLT) is a promising non-pharmacological treatment for a range of psychiatric conditions. The goal of this review was to provide a comprehensive overview of the efficacy of BLT across mental and behavioral illnesses. Using systematic umbrella review methodology, we searched Ovid MEDLINE, Embase, PsycInfo, Web of Science, and Google Scholar for systematic reviews of randomized controlled trials (RCTs) evaluating BLT for any mental or behavioral illness from the date of inception until March 2021. Review quality was assessed using the AMSTAR 2 tool and summary efficacy data were extracted from recent reviews. Of 792 unique records, 67 systematic reviews were included which targeted a range of disorders related to mood, neurocognition, sleep, and eating. Recent meta-analyses targeting seasonal or non-seasonal depression found that BLT outperformed light-related control conditions. Reviews of other disorders identified few RCTs and generally did not support the efficacy of BLT for various outcomes. Overall, the extant literature supports the efficacy of BLT for seasonal and non-seasonal depression, although higher quality systematic reviews are needed to increase confidence in these findings. There was no specific funding for this review, and it was preregistered on Prospero (ID: CRD42021240751).